Growth and kinetic studies of emergent plants in the presence of phosphate. - Sai, Tu Jian. (2010)
Excessive phosphate loaded into aquatic systems can result in eutrophication which severely reduces water quality and causes undesirable disturbance to ecosystem health. Conventional water treatment technologies for phosphate removal are expensive and can consume high amount of energy. This project aims to investigate the phosphate phytoremediation potential of ten emergent plants under controlled greenhouse conditions: Acanthus ebracteatus, Acanthus ilicifolius, Acorus gramineus, Ceratopteris thalictroides, Echinodorus palaefolius, Equisetum hyemale, Lepironia articulata, Mentha aquatica, Portulaca oleracea and Ruellia brittoniana. All the plants displayed zero-order kinetics for phosphate uptake, and significant reduction in phosphate level when compared to the control experiment. P. oleracea exhibited the highest growth rate of 6.7 ± 1.07 % day-1 and 9.8 ± 2.25 % day-1 based on fresh mass and dry mass respectively. The highest removal rate was exhibited by A. ilicifolius at 18.6 ± 3.52 μM g-1fresh wt day-1 and A. gramineus at 36.3 ± 6.90 μM g-1dry wt day-1. Certain plants from the above list were selected for an application study using the lab-fabricated continuous flow phosphate phytofiltration system which simulates the concept of “biotope”. The results indicated that plants can indeed provide a cheaper and sustainable solution for phosphate removal in waterways and waterbodies.